Response of market price relative to fundamentals of stocks : a case based approach on pharmaceutical industry listed in DSE - Faruquee, Murtaza (BRAC University, 2013)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2013.